(untitled) (Orfeu, 2020)
Rhetoric has its birth and development in Greece and later in Rome, reaching all of Europe at the end of Antiquity and extending to the Middle Ages, contributing to the enrichment of various spheres of human knowledge, as well as music. The contact between the two arts takes place, from the 16th century through treaties ranging from German, French, Italian, and Portuguese composers, reaching then, to Brazilian musicians students in the metropolis, the conscious knowledge of the use of elements and techniques that establish, among other possibilities, greater adherence to the audience. Located in this framework is Luís Álvares Pinto, Brazilian composer and teacher who, through his contact with humanistic studies, brought to his work Te deum Laudamus possible figures that characterize the applicability of rhetoric in his music.